Epigenetics in the public sphere: interdisciplinary perspectives. Issue 4 (24th October 2019) - Dubois, Michel; Louvel, Séverine; Le Goff, Anne; Guaspare, Catherine; Allard, Patrick
Abstract: Despite the high public interest in epigenetics, few scholars have empirically investigated the forms, reasons and consequences of the public circulation of epigenetics. Using an original database focusing on 'lifestyle' or 'everyday' epigenetics, this article aims to promote an open-minded and interdisciplinary dialogue between the public appropriation of epigenetics and the current scientific state of the art. It raises three main questions: Are there any specific modes of circulation of epigenetics in the general public? Why does epigenetics seem so appealing to the public? Within the public repertoire of epigenetics, is it possible to identify some specific knowledge claims and, if so, given the current state of the art, what is their degree of accuracy? The article argues that the social diffusion of epigenetics frequently carries on beliefs and misconceptions about genetics and epigenetics. The social life of epigenetics fuels a collective 'illusion' of control and empowerment on the basis of which new markets expand. More unexpectedly, this article underlines the emergence of a new scientific culture, i.e. the 'scientifization' of the cultural appropriation of epigenetics. Our analysis can inform the scientific community about the current and evolving state of the public representation of epigenetics and help it frame outreach activities.